2021
DOI: 10.1177/00469580211060790
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Willingness to pay for Employment-Based Health Insurance Among Governmental School Workers in Saudi Arabia

Abstract: School workers constitute the bulk of public workers in Saudi Arabia. Most of these workers seek public health care services through the Ministry of Health, which is characterised by an overloaded service. Consequently, the government is planning to introduce employment-based health insurance. However, government employees’ willingness to pay (WTP) for health insurance was not investigated. This study explores the feasibility and acceptability of employment-based health insurance by examining public school wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 20 publications
3
9
1
Order By: Relevance
“…The findings showed that approximately 50% of government employees would be happy to contribute to and purchase the proposed health insurance program. Nonetheless, the proportion of individuals who would willingly purchase health insurance (49.6%) was found to be lower than in a previous study (77.9%), which was carried out amongst public school workers in Saudi Arabia [18]. Other studies performed in the context of Saudi Arabia have revealed that a higher percentage of participants would be happy to purchase national health insurance.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…The findings showed that approximately 50% of government employees would be happy to contribute to and purchase the proposed health insurance program. Nonetheless, the proportion of individuals who would willingly purchase health insurance (49.6%) was found to be lower than in a previous study (77.9%), which was carried out amongst public school workers in Saudi Arabia [18]. Other studies performed in the context of Saudi Arabia have revealed that a higher percentage of participants would be happy to purchase national health insurance.…”
Section: Discussioncontrasting
confidence: 80%
“…The mean WTP for health insurance identified in this study was higher than in other studies carried out in Saudi Arabia. For example, a study among workers in public schools in Riyadh found that individuals would be willing to pay 77.9 SAR per month (US$ 20.7) on average for an employment-based health insurance policy [18]. A further study performed by [15] with the general population revealed that households were willing to pay a mean amount of 50 SAR (US$ 13.3) per family per month [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations